2006
DOI: 10.1080/00140130600858142
|View full text |Cite
|
Sign up to set email alerts
|

The impact of light and colour on psychological mood: a cross-cultural study of indoor work environments

Abstract: The aim of the study was to determine whether indoor lighting and colour would have any systematic impact on the mood of people working indoors. Earlier studies have mostly focused either on light, colour or windows in laboratory settings. The present study was carried out in real work environments at different seasons and in countries with different latitudes. A total of 988 persons completed all parts of the study. In the countries situated far north of the equator there was a significant variation in psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
165
3
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 278 publications
(187 citation statements)
references
References 21 publications
4
165
3
6
Order By: Relevance
“…Like sleeping temperature, ideal levels of light are also variable and no one level of light suits all individuals (Küller, et al 2006, Caspari, et al, 2006. To experience comfortable levels of light it is therefore important for individuals to have some control over light levels in their environments.…”
Section: Light In Cabinsmentioning
confidence: 99%
“…Like sleeping temperature, ideal levels of light are also variable and no one level of light suits all individuals (Küller, et al 2006, Caspari, et al, 2006. To experience comfortable levels of light it is therefore important for individuals to have some control over light levels in their environments.…”
Section: Light In Cabinsmentioning
confidence: 99%
“…coloured walls) on mood suggest that the right amount of ambient colour can improve the mood of people. Küller and colleagues [2] found that office workers which judged their offices as colourful experienced a better mood throughout the year than office workers that judged their offices as neutral or colourless.…”
Section: Introductionmentioning
confidence: 99%
“…How people experience the affective meaning of these ambiences is referred to as atmosphere perception. In addition, it is known that colour can affect people's mood [2]. Hence, we believe that also (coloured) lighting ambiences have the potential to improve the mood and emotional state of the people occupying a room.…”
Section: Introductionmentioning
confidence: 99%
“…Providing quality daylighting is desirable to support long hours spent in working spaces to ensure optimum productivity, task visibility, alertness, and positive health outcomes [6]. Research has shown that daylighting effects visual performance, biological rhythms, visual stimulation, mood, safety and, the perceived quality of the work environment [7][8][9][10]. For instance, the amount of daylight penetrating from windows into interior offices can have a positive influence on job satisfaction, support well-being, and relaxation [11][12][13].…”
Section: Introductionmentioning
confidence: 99%